KONSEP AMANAT AGUNG BERDASARKAN MATIUS 28:1820 DALAM MISI - Batholomeus Diaz Nainggolan (Fakultas Filsafat Universitas Advent Indonesia, 2014)
Involvement in mission is an obligation that must be carried by all membersof the Seventh-day Adventist Church. Mission is not an option to be done or not done.Mission is God's heart, His is a command to be implemented by all his people.Involvement in the mission can be divided into two different categories according tothe Lord's call. The first category are those who are called to engage directly in themission field as a missionary. The second category are those who are called to bemissionaries senders.